Pharmacokinetics, Safety, and CCR2/CCR5 Antagonist Activity of Cenicriviroc in Participants With Mild or Moderate Hepatic Impairment. Issue 3 (12th May 2016) - Lefebvre, E; Gottwald, M; Lasseter, K; Chang, W; Willett, M; Smith, PF; Somasunderam, A; Utay, NS
Abstract : Cenicriviroc, a dual CCR2/CCR5 antagonist, is being evaluated for treatment of nonalcoholic steatohepatitis and liver fibrosis (CENTAUR; NCT02217475). As it is metabolized by the liver, cenicriviroc was investigated in hepatic‐impaired participants for pharmacokinetic changes. Participants with mild‐to‐moderate hepatic impairment (HI) (Child–Pugh class A ( N = 7) or B ( N = 8)) and matched controls ( N = 15) received cenicriviroc 150 mg once daily for 14 days. Serial blood samples were obtained on Days 1 and 14. Safety, tolerability, and effects on CCR2/CCR5 ligands, cytokines, and bacterial translocation biomarkers were evaluated. Cenicriviroc exposures were increased by moderate HI (AUC0‐τ 55%, Cmax 29% higher) but were not with mild HI (AUC0‐τ 38%, Cmax 40% lower). Cenicriviroc was well tolerated. Rapid and potent CCR2/CCR5 blockade was observed, not associated with increases in hepatic inflammation or bacterial translocation biomarkers. Study findings suggest that cenicriviroc 150 mg can be used in patients with mild‐to‐moderate HI.